[Translated article] Primary Cutaneous Lymphoma Registry of the Spanish Academy of Dermatology and Venereology (AEDV): Data for the First 5 Years - D. Falkenhain-López; C. Muniesa; M.T. Estrach; M. Morillo-Andújar; Y. Peñate; E. Acebo; R.M. Pujol; M.P. García-Muret; S. Machan; S. Medina; R. Botella-Estrada; R. Fernández de Misa; et al. (Actas Dermo-Sifiliográficas, 2023)
Background and objective: Primary cutaneous lymphomas (PCL) are uncommon. Observations based on the first year of data from the Spanish Registry of Primary Cutaneous Lymphomas (RELCP, in its Spanish abbreviation) of the Spanish Academy of Dermatology and Venereology (AEDV) were published in February 2018. This report covers RELCP data for the first 5 years. Patients and methods: RELCP data were collected prospectively and included diagnosis, treatments, tests, and the current status of patients. We compiled descriptive statistics of the data registered during the first 5 years. Results: Information on 2020 patients treated at 33 Spanish hospitals had been included in the RELCP by December 2021. Fifty-nine percent of the patients were men; the mean age was 62.2 years. The lymphomas were grouped into 4 large diagnostic categories: mycosis fungoides/Sézary syndrome, 1112 patients (55%); primary B-cell cutaneous lymphoma, 547 patients (27.1%); primary CD30+ lymphoproliferative disorders, 222 patients (11%), and other T-cell lymphomas, 116 patients (5.8%). Nearly 75% of the tumors were registered in stage I. After treatment, 43.5% achieved complete remission and 27% were stable at the time of writing. Treatments prescribed were topical corticosteroids (1369 [67.8%]), phototherapy (890 patients [44.1%]), surgery (412 patients [20.4%]), and radiotherapy (384 patients [19%]). Conclusion: The characteristics of cutaneous lymphomas in Spain are similar to those reported for other series. The large size of the RELCP registry at 5 years has allowed us to give more precise descriptive statistics than in the first year. This registry facilitates the clinical research of the AEDV's lymphoma interest group, which has already published articles based on the RELCP data. Resumen: Antecedentes y objetivos: Los linfomas cutáneos primarios (LCP) son un conjunto de entidades poco frecuentes. En febrero del 2018 se describieron los resultados del primer año de funcionamiento del Registro de linfomas cutáneos primarios de la AEDV. En el presente trabajo actualizamos los resultados tras 5 años de funcionamiento. Pacientes y métodos: Registro de enfermedad de pacientes con LCP. Se recogieron datos prospectivamente de los pacientes, incluyendo diagnóstico, tratamientos, pruebas realizadas y estado actual del paciente. Se realizó un análisis descriptivo. Resultados: En diciembre del 2021 se había incluido a un total de 2.020 pacientes en el Registro, pertenecientes a 33 hospitales españoles. El 59% fueron hombres, y la edad media fue de 62,2 años. Se agruparon en 4 grandes grupos diagnósticos: micosis fungoide/síndrome de Sézary (1.112 [55%]), LCP de células B (547 [27,1%]), trastornos linfoproliferativos de células T CD30+ (222 [11%]) y otros linfomas T (116 [5,8%]). La mayoría presentó estadio T1, encontrándose actualmente casi el 75% en remisión completa (43,5%) o enfermedad estable (EE: 27%). Los tratamientos más usados fueron corticoides tópicos (1.369 [67,8%]), fototerapia (890 [44,1%]), cirugía (412 [20,4%]) y radioterapia (384 [19%]). Conclusión: Las características del paciente con LCP en España no difieren de otras series. El mayor tamaño del registro permite precisar mejor los datos con respecto a los resultados del primer año. Este registro facilita al grupo de linfomas de la AEDV realizar investigación clínica, surgiendo ya trabajos publicados de dicho registro.